Computerized Stroop Test to Assess Selective Attention in Children with Attention Deficit Hyperactivity Disorder - Capovilla, Fernando Cesar; Assef, Ellen Carolina Dos Santos; Capovilla, Alessandra Gotuzo Seabra (The Spanish Journal of Psychology, 2007)
Research shows abnormal function of the pre-frontal cortex in Attention Deficit Hyperactivity Disorder (ADHD). This cortex is involved in the control of executive functions related to planning and execution of goal-oriented strategies, working memory, inhibitions, cognitive flexibility, and selective attention. Selective attention involves focus on the target stimulus, ignoring competing distractions. The Stroop Test (Stroop, 1935) is usually used to evaluate selective attention. This study investigated whether children with ADHD could exhibit modified performance in the Stroop Test. Using a computerized version of this test (Capovilla, Montiel, Macedo, & Charin, 2005), the study compared the reaction times (RTs) of 62 Brazilian children, between 8 and 12 years of age, 31 of whom were diagnosed with ADHD and sent to psychiatric clinics, and 31 without ADHD studying in regular schools. All children with ADHD satisfied the criteria of the DSM-IV-TR and were evaluated with the Conners Abbreviated Questionnaire (Goyette, Conners, & Ulrich, 1978), completed by parents and teachers. The results revealed that children with ADHD exhibit greater interference in RT than children without ADHD. This corroborated the hypothesis that children with ADHD exhibit a deficit in selective attention, consisting in augmented RTs, as measured by the Computerized Stroop Test.
Keywords: Stroop Tes; ADHD; Neuropsychology; Selective attention; Executive functions